The Culture of Showing Off and the Hegemony of Social Status in the Short Film Pamean by Paniradya Kaistimewan - Muhammad Iqbal Ramadhan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze how the culture of showing off is displayed through the character of Bu Sumirah and how social status is negotiated through objects, language, and communication relations with the character Asih in the short film Pemean by Paniradya Kaistimewan. This study uses a qualitative approach. The main data are dialogues, character actions, object symbols, and the setting of the drying room in the film Pemean. The analysis is carried out by reading key scenes that display expensive clothes, branded batik, expensive coffee, and motorbikes as symbols of social status. Antonio Gramsci's theoretical framework is used to understand the hegemony of social status, while Jürgen Habermas's thoughts are used to read unequal communication in the relationships between characters. The results show that the culture of showing off in Pemean does not only appear as a personal trait of Bu Sumirah, but as a social phenomenon born from the pressure to appear capable, classy, ​​and worthy of admiration. The items on display function as markers of prestige and a tool to build social distance with Asih. However, when the items are proven to be borrowed, Bu Sumirah's social image begins to collapse. The film ultimately critiques the culture of appearance that judges people based on possessions, the price of goods, and social recognition, while also showing the fragility of social status built on falsehood.